2010
DOI: 10.4314/ajem.v8i1.57575
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome among patients with type 2 diabetes mellitus in Uyo, Nigeria

Abstract: Background:The metabolic syndrome is a cluster of risk factors that is responsible for most of the excess cardiovascular morbidity amongst persons with type 2 Diabetes Mellitus (DM). The metabolic syndrome increases the risk for coronary heart disease and stroke by three-fold with a marked increase in cardiovascular mortality. Objectives: This study set out to find the prevalence of the metabolic syndrome amongst type 2 diabetes mellitus patients and the commonest metabolic abnormalities in them in Uyo, South-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 10 publications
5
19
1
1
Order By: Relevance
“…Diabetes has become a great economic challenge as it drains between 5- excessive intake of calories . This contributes to obesity [2] which is a risk factor for development of diabetes . We are seeing an increasing incidence of type 2 diabetes in the [2] young as a result of obesity .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetes has become a great economic challenge as it drains between 5- excessive intake of calories . This contributes to obesity [2] which is a risk factor for development of diabetes . We are seeing an increasing incidence of type 2 diabetes in the [2] young as a result of obesity .…”
Section: Introductionmentioning
confidence: 99%
“…This contributes to obesity [2] which is a risk factor for development of diabetes . We are seeing an increasing incidence of type 2 diabetes in the [2] young as a result of obesity . It is important to know about the awareness level of this condition as knowledge is a [2] critical component of behavioral change .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated rapidly rising prevalence rates globally [1]. Prevalence rates in Nigeria have been estimated to be between 16-35% in the general population [2][3][4] and 25-86% among subjects with type-2 diabetes (T2D) [5][6][7][8]. Most of the studies done on the prevalence of metabolic syndrome in Nigeria have been on T2D patients.…”
Section: Introductionmentioning
confidence: 99%